Ecological Study of a Lentic Water Body In Relation To Bacterial Population (International Journal of Scientific Research and Management (IJSRM), 2016)
Physico-chemical analysis and study of bacterial population were carried out on water samples of Kavalkere pond in Bannerghatta Biological Park, Bangalore. The bacterial population abundance largely depend on the physico-chebmical conditions prevailing in the water of the pond. The study shows the importance of heterotrophic food chain in the trophic characteristics of a lentic water system